TREATMENT OF CLASS I MALOCCLUSION WITH MILD CROWDING AND MIDLINE SHIFT - Edwin Triwidianto; Ida Bagus Narmada (Dentino : Jurnal Kedokteran Gigi, 2020)
ABSTRACT  Background: The main goal of orthodontic treatment is to obtain a normal relationship of the teeth with facial structures and it is generally accepted that orthodontic treatment will have effects on facial proportion. Nowadays, facial appearance has a big influence on someone's appearance. Aesthetic facial appearance will produce a proportional, harmonious, and youthful facial profile. Case: this case report aims to describe that non extraction orthodontic treatment in class I malocclusion with mild crowding and mildline shift is a treatment with considerable success. Case management: A 19 years old female came with a chief complaint of crowding in upper and lower jaw. Intraoral examination revealed bilateral Class I molar and canine relationship. Patient had crowding in upper and lower jaw, and midline shift in lower jaw. Extra oral findings included a flat profile with competent lips. Cephalometric analysis showed skeletal class I with orthognati maxilla and mandible. Patient was bonded with 0.022-inch MBT brackets orthodontic appliance without extraction.  After 20 months of treatment, an ideal arch coordination was achieved, the patient felt confident and satisfied with the treatment outcome. Conclusion: Decision to extract a tooth has to be made, not only by considering the amount of crowding, but also the eventual influence of orthodontic tooth displacement on the soft tissue surface of the face. Keywords: Crowding, Midline shift, Non – extraction.